2014
DOI: 10.1177/2329496514524926
|View full text |Cite
|
Sign up to set email alerts
|

Social Desire Paths

Abstract: Using insights from landscape architecture on how pedestrian-driven “desire paths” inform the design of public landscapes, I offer a new concept for sociologists to consider—social desire paths. The social desire path metaphor puts attention on instances when there are disconnects between formal structures and what individuals actually do in the course of action. Conscious or not, such paths, which commence at the individual level, often become collective and leave an imprint on social structures. When identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Thus, the skills that the learner is not willing to learn and has unpleasant experiences leave him with a reality and a negative effect on himself that he cannot practice and train on. This corresponds to (Thorndike's) laws of learning, namely, "availability rudiment of connectionism claims that students can gain the ease of using knowledge permanently in many different occasions after the learning stages are completed, and the accurate connections are made between the relevant data" 15,16 . If people begin to exercise, they may become more familiar with the physical sensations of exercise, experience less discomfort as they become fit, experience desirable mood changes when they exercise, and begin to enjoy physical activity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, the skills that the learner is not willing to learn and has unpleasant experiences leave him with a reality and a negative effect on himself that he cannot practice and train on. This corresponds to (Thorndike's) laws of learning, namely, "availability rudiment of connectionism claims that students can gain the ease of using knowledge permanently in many different occasions after the learning stages are completed, and the accurate connections are made between the relevant data" 15,16 . If people begin to exercise, they may become more familiar with the physical sensations of exercise, experience less discomfort as they become fit, experience desirable mood changes when they exercise, and begin to enjoy physical activity.…”
Section: Discussionmentioning
confidence: 91%
“…Use characters to indicate meaning (A=Arithmetic mean, D=Standard deviation& L=Standard level). The lowest level of response was determined for the measure of social desire (10) degrees, the maximum range (20), the mean medium of the scale (15) In order to determine the correlation between the independent variables and the dependent variable skills have determined correlation coefficient values. It was found that the correlative relationship between social desirability and artistic gymnastic skills all determined a positive correlation relationship with the least value (0.24) in balance skills, the highest value (0.58) was with the handstand skill.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of practices pertaining to the inhabitants are in fact immersed in a continuous flux of changes: to social needs, lifestyles, living cultures, the composition of basic social units, etc. (Norman 2011;Gehl 2010). Habitation is, in other words, profoundly temporal.…”
Section: Two Sets Of Intentionsmentioning
confidence: 99%
“…Finally, a third subset of the intersection between potential and actual spaces, namely the enacted space (Subset 3 in Figure 2), represents the totality of actions given substance by the inhabitants to compensate for the requirements not met by the design (Norman 2011). This form of social production of space-to quote, although with a rather different meaning, an expression used by Lefebvre (1974), one of the few authors to assume the space and the practices relating to it as a founding analytical category-is the set of adaptive practices that represent an attempt by the inhabitants to modify, alter, and self-design a space that fulfills their actual requirements (Fuller 2017).…”
Section: Investigating Potential and Actual Space Relationship: Text-...mentioning
confidence: 99%